2014
DOI: 10.1182/blood.v124.21.3092.3092
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Escalated, Intratumoral TLR9 Agonist and Low-Dose Radiation Induce Abscopal Effects in Follicular Lymphoma

Abstract: Abscopal effects, systemic tumor regression following localized therapy, are induced by radiation therapy and augmented with intratumoral immunostimulation. Based on a preclinical lymphoma model, we previously investigated low-dose immunostimulation with a Toll-like receptor 9 (TLR9) agonist in combination with fractionated, low-dose radiation therapy in relapsed/refractory NHL (NCT00185965) and Mycosis Fungoides (NCT00226993). In an attempt to improve the potency of the immune responses and the rate of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Type B TLR9 agonists preferentially activate B cells (versus plasmacytoid DC). The type B TLR9 agonist Agatolimod (PF‐ 3512676) has been used in the greatest number of clinical trials, including three trials using a combination of low‐dose irradiation and intratumoral CpG administration showing promising results in 60 patients with low‐grade B‐cell lymphoma and mycosis fungoides including partial and complete remissions, lasting up to >4 years (Brody et al., 2010; Kim et al., 2012; Kohrt et al., 2014). A study of intracerebral (intratumoral) infusion of another type B TLR9 agonist Litenimod (CpG‐28) in 34 patients with recurrent glioblastoma multiforme also showed efficacy in controlling disease burden yielding 1 and 2 year survival rates higher than historical controls (Carpentier et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Type B TLR9 agonists preferentially activate B cells (versus plasmacytoid DC). The type B TLR9 agonist Agatolimod (PF‐ 3512676) has been used in the greatest number of clinical trials, including three trials using a combination of low‐dose irradiation and intratumoral CpG administration showing promising results in 60 patients with low‐grade B‐cell lymphoma and mycosis fungoides including partial and complete remissions, lasting up to >4 years (Brody et al., 2010; Kim et al., 2012; Kohrt et al., 2014). A study of intracerebral (intratumoral) infusion of another type B TLR9 agonist Litenimod (CpG‐28) in 34 patients with recurrent glioblastoma multiforme also showed efficacy in controlling disease burden yielding 1 and 2 year survival rates higher than historical controls (Carpentier et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, for many other cancer types, systemic or intra-tumoral delivery of TLR7 agonists may be required to elicit anti-tumor immune responses. Recent preclinical and clinical studies have demonstrated the immunogenicity of TLR agonists when delivered intra-tumorally [ 19 , 20 ]. However, direct intratumoral administration to non-cutaneous tumors requires image-guided delivery and may be challenging where repeated administration is required.…”
Section: Discussionmentioning
confidence: 99%
“…injection of ipilimumab with local irradiation, is being investigated for the treatment of lymphoma, melanoma, colon, and rectal cancer (NCT01769222). A TLR-9 agonist administered intratumorally to B cell lymphoma [81] and follicular lymphoma patients [98] showed effective anti-tumor response. Moreover, one phase 1 trial indicated that s.c. administration of the anti-PD-1 PF-06801591, is a feasible and effective alternative to i.v.…”
Section: Site and Route Of Deliverymentioning
confidence: 99%